(untitled) (Vietnam Journal of Community Medicine, 2026)
Acute toxicity is a fundamental criterion in the preclinical safety evaluation of herbal medicinal preparations. However, the scientific basis for explaining the safety of traditional medicine formulas, particularly those with modified and combined compositions, remains limited when considering the interactions among their constituent components. This review aims to analyze the acute toxicity of the Tieu Doc Duong Phu formula from an integrative perspective combining modern pharmacology and traditional medicine theory. Experimental data indicate that the liquid extract of Tieu Doc Duong Phu does not cause mortality, behavioral abnormalities, or physiological dysfunction, and no LD₅₀ could be determined at the maximum tolerated dose, suggesting a high safety profile under acute toxicity testing conditions. From the standpoint of modern pharmacology, safety is assessed through standard acute toxicity parameters. In traditional medicine theory, safety is interpreted through the principle of herbal compatibility, which regulates pharmacological properties, maintains the balance of qi, blood, and body fluids, and minimizes the generation of medicinal toxicity. The convergence of these two approaches highlights the central role of formulation compatibility in ensuring the safety of the formula at the level of acute toxicity.